Development of a Very High Cycle Fatigue (VHCF) multiaxial testing device (Fracture and Structural Integrity, 2016)
The very high cycle region of the S-N fatigue curve has been the subject of intensive research on the last years, with special focus on axial, bending, torsional and fretting fatigue tests. Very high cycle fatigue can be achieved using ultrasonic exciters which allow for frequency testing of up to 30 kHz. Still, the multiaxial fatigue analysis is not yet developed for this type of fatigue analyses, mainly due to conceptual limitations of these testing devices. In this paper, a device designed to produce biaxial fatigue testing using a single piezoelectric axial exciter is presented, as well as the preliminary testing of this device. The device is comprised of a horn and a specimen, which are both attached to the piezoelectric exciter. The steps taken towards the final geometry of the device are presented. Preliminary experimental testing of the developed device is made using thermographic imaging, strain measurements and vibration speeds and indicates good behaviour of the tested specimen.
Keywords: Multiaxial fatigue; Very high cycle fatigue; Fatigue testing machines; Strain measurements